2008
DOI: 10.1007/s11524-008-9271-1
|View full text |Cite
|
Sign up to set email alerts
|

Greater Drug Injecting Risk for HIV, HBV, and HCV Infection in a City Where Syringe Exchange and Pharmacy Syringe Distribution are Illegal

Abstract: Comparing drug-injecting risk between cities that differ in the legality of sterile syringe distribution for injection drug use provides a natural experiment to assess the efficacy of legalizing sterile syringe distribution as a structural intervention to prevent human immunodeficiency virus (HIV) and other parenterally transmitted infections among injection drug users (IDUs). This study compares the parenteral risk for HIV and hepatitis B (HBV) and C (HCV) infection among IDUs in Newark, NJ, USA, where syring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…Moreover, NIUs who use heroin may be more likely to have sexual partnerships with IDUs because the main drug of choice among many IDUs is also heroin. In NYC, for example, 90% of IDUs in one study reported that they injected heroin (Neaigus et al, 2008). Drug users who use the same drug of choice may be more likely to develop social and sexual relationships with each other.…”
Section: Not At Parenteral Risk Of Hiv Infection Nius Remain At Riskmentioning
confidence: 99%
“…Moreover, NIUs who use heroin may be more likely to have sexual partnerships with IDUs because the main drug of choice among many IDUs is also heroin. In NYC, for example, 90% of IDUs in one study reported that they injected heroin (Neaigus et al, 2008). Drug users who use the same drug of choice may be more likely to develop social and sexual relationships with each other.…”
Section: Not At Parenteral Risk Of Hiv Infection Nius Remain At Riskmentioning
confidence: 99%
“…The information generated through these bio-behavioral studies would be of great importance in estimating the future burden of HCV in the MENA region, in addition to its impact on the introduction of intervention programs, such as needle/syringe exchange programs. Needle/syringe exchange programs have been shown to reduce the risk of transmission of HIV, HCV, and hepatitis B virus (HBV), and are now being implemented in many parts of the world, including developing countries, such as China and India [149][150][151]. The introduction of such programs in the MENA region presents a formidable challenge due to religious and social factors.…”
Section: Challenges and Recommendationsmentioning
confidence: 99%
“…Although ecological data are subject to the ecological fallacy [37], the biobehavioral surveys that have linked a history sharing HDSS to testing positive for HIV antibodies provide preliminary evidence of a link at the individual level. Comparisons of HIV prevalence among PWID in cities where all PWID use LDSS exclusively and in cities where substantial numbers of PWID use HDSS can serve as natural experiments, if sufficient data are available to rule out alternative explanations [38].…”
Section: Findings From Ecological Studies Are Consistent With the Matmentioning
confidence: 99%